An Analysis of Non-Vocal Backchannels of The Indonesian Presidential Candidates on The Second Debate 2019 - Ambar Rahmawati; Eli Diana; Nopriansah Nopriansah (Literary Criticism, 2020)
Abstract The aims of the study is to analyze Non-Vocal Backchannels of the Indonesian Presidential Candidates on The Second Debate 2019. This research has two objectives: first, to identify Non-Vocal Backchannels that used by The Presidential Candidates on the second debate. Second, to analyze the function of Backchannels used by the presidential candidates on the second debate. This research employed a descriptive qualitative method. It is concerned with the description of the data in the form of conversation from the presidential candidates’ debate based on Yule's theories of Backchannels and function of backchannels. Based on the obtained result, it can be concluded thatthe most dominant of non-vocal backchannels of the presidential candidates on the second debate is Eye Gaze and The most frequently performed function is Continuer and Acknowledgement. Keyword: Pragmatics, Backchannels, Presidential Debate.